Employee training policies of high revenue companies: Analysis of case examples from turkey - Betül Balkar; Nazife Karadağ (International Journal for Research in Vocational Education and Training (IJRVET), 2024)
Purpose: The present study explores the primary characteristics of employee training practices by way of analysing the employee training policies of the top two companies with the highest sales revenue in Turkey. The primary characteristics of employee training practices are examined within the scope of the corporate employee training activities and the practices to cope with the challenges in the organization of employee training. Methods: Employing qualitative approach, document analysis was conducted within the context of two cases. The two companies with the highest sales revenue in Turkey were selected as cases in the study. The companies were determined through criterion sampling in line with the financial performance based on net sales revenue, stability of financial performance and potential for corporate training policy development criteria. The six years of sustainability and activity reports of the companies were analysed through thematic analysis. The documents were analysed through thematic analysis using open coding. Employee training policies and practices were presented under the sub-themes of personnel training types, subjects of personnel training, training infrastructure, factors considered in the design of training processes and supportive practices for training processes. Findings: Employee training of the companies mostly consists of formal and non-formal training activities designed according to the needs of employees. These training activities aim at both occupational and personal development of the employees. The training activities, which are mostly organized with the use of internal resources, also allow employees to make their own personal development plans. The dominant common aspects of the employee training policies of the companies show that the successful integration of employee training to the career management systems increases the efficiency of training activities. The study results also illustrate that the employee training policies can be strengthened through corporate capacity development activities. Conclusion: Institutionalization of training practices that contribute to workplace learning has an important role in the financial gains of highly competitive organizations. The success of corporate training practices for employees requires both an effective design in terms of content and process and a strong establishment of corporate training infrastructure. The provision of formal and informal learning opportunities structured according to employee needs through a strong corporate training infrastructure and planning the career development of employees based on the outputs of training activities are the indicators of successful company performance.
Keywords: 330; Corporate Training Policies; Employee Training; Financial Performance; Turkey; VET; Vocational Education and Training; Workplace Learning